Clinicopathologic features and prognostic value of KRAS, NRAS and BRAF mutations and DNA mismatch repair status: A single‐center retrospective study of 1, 834 Chinese patients with Stage I–IV colorectal cancer. Issue 6 (22nd June 2019) - Guo, Tian‐An; Wu, Yu‐Chen; Tan, Cong; Jin, Yu‐Tong; Sheng, Wei‐Qi; Cai, San‐Jun; Liu, Fang‐Qi; Xu, Ye
Abstract : Mutations of KRAS, NRAS, BRAF and DNA mismatch repair (MMR) status have become an important part of the assessment of patients with colorectal cancer (CRC), while respective clinicopathologic features and prognostic significance in specific stages and related detection strategies remain unclear. We retrospectively analyzed clinicopathologic features and prognosis of 1, 834 patients with Stage I–IV colorectal adenocarcinoma. Mutations in KRAS, NRAS and BRAF and DNA MMR status were determined. The mutation rates of KRAS, NRAS and BRAF were 46.4, 3.2 and 3.5%, respectively, and the mismatch repair gene deletion (dMMR) rate was 5.6%. In a multivariate analysis, female, advanced age, tumor type histology, mucinous carcinoma and positive tumor deposits were associated with a high KRAS mutation rate. A high BRAF mutation rate was associated with female, poor differentiation, lymphovascular invasion and positive tumor deposits. Factors associated with high dMMR rates included low age, large tumor size, poor differentiation, Stages I–III. Tumor site was independently associated with KRAS mutation, BRAF mutation and dMMR. KRAS and BRAF mutations were independent risk factors for shorter overall survival (OS) in Stage IV tumors but not in Stage I–III tumors. NRAS mutation was an independent risk factor for shorter OS in Stage I–II tumors. dMMR was independently associated with longer OS in Stage III tumors. Abstract : What's new? Mutations in KRAS, NRAS, BRAF and DNA mismatch repair (MMR) status are important biomarkers in the assessment of patients with colorectal cancer (CRC). However, the clinicopathologic features associated with these mutations—and their impact on prognosis—are unclear, especially at earlier stages of CRC. In this large Chinese study, the authors analyzed variables such as gender, age, tumor histology, lymphovascular invasion, etc., that were associated with particular oncogene mutations and overall survival. These results should provide guidance for improved clinical strategies and enhance the usefulness of these biomarkers.